Wanting to provide the childhood they never got – a meta-synthesis of how survivors of childhood abuse experience becoming a parent - Signe Hjelen Stige; Martin Mauritzson Greve; Kari Anne Trefall (International Journal of Qualitative Studies on Health & Well-Being, 2025)
Purpose Experiencing childhood abuse is associated with an increased risk of developing a broad range of health issues and might impact the experience of transitioning into parenthood. We therefore wanted to explore how survivors of childhood abuse experience becoming a parent. Methods Using the method of meta-ethnography, we synthesized the findings from 13 primary studies. Results The meta-synthesis resulted in three themes: 1) Own experiences of abuse enhance the desire to be a good parent; 2) Own experiences of abuse challenges parents in their new role; and 3) Becoming a parent as an opportunity to start a healing process. Conclusion Our results indicated that parents shared a dedication to providing their children with a better childhood than they had experienced. However, many parents struggled with low self-efficacy, and several became aware of their difficulties with attachment and emotional regulation when they became parents. Although challenging, the parenting role was also a source of positive and healing experiences. The implications of these results are discussed.